Modified 2, 6-diamino-3, 5-dinitropyrazine-1-oxide-based hybrid energetic material with high decomposition rate as well as preparation method and application of modified 2, 6-diamino-3, 5-dinitropyrazine-1-oxide-based hybrid energetic material

By introducing the crosslinking reaction of the high-nitrogen two-dimensional material TAGP in LLM-105, the problem of improving the thermal decomposition rate of LLM-105 is solved, and a 50% decomposition rate increase and high safety is achieved. It is suitable for high-energy safe propellant charges .

CN119241451AActive Publication Date: 2025-01-03NORTHWESTERN POLYTECHNICAL UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411518270.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-03
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

The prior art is difficult to significantly increase the thermal decomposition rate of 2,6-diamino-3,5-dinitropyrazine-1-oxide (LLM-105), limiting its application potential in the field of propellants.

Method used

TAGP is generated by cross-linking glyoxaldehyde or glutaraldehyde with triaminoguanidine nitrate. Using TAGP as a template material, LLM-105 is induced to crystallize under its confined domain constraints to form a modified LLM with a high decomposition rate -105-based hybrid energy-containing material.

Benefits of technology

It significantly improves the thermal decomposition rate of LLM-105, which increases the decomposition rate by 50%, while maintaining high safety, and is suitable for the field of high-energy safety propellant charges.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241451A_ABST
    Figure CN119241451A_ABST
Patent Text Reader

Abstract

The invention discloses a modified 2, 6-diamino-3, 5-dinitropyrazine-1-oxide-based hybrid energetic material with a high decomposition rate as well as a preparation method and application of the modified 2, 6-diamino-3, 5-dinitropyrazine-1-oxide-based hybrid energetic material, and relates to the technical field of composite materials. The method comprises the following steps: firstly, obtaining an energetic high-nitrogen two-dimensional material (TAGP) formed by crosslinking triaminoguanidine nitrate (TAGN) and an aldehyde solvent, then inducing LLM-105 to crystallize by taking TAGP as a template material, and separating, washing and drying to obtain the LLM-105 / TAGP composite energetic material. The LLM-105-based composite energetic material provided by the invention has the characteristic that the thermal decomposition rate is greatly improved, compared with an LLM-105 raw material, the decomposition rate is improved by 50%, and meanwhile, the composite energetic material gives consideration to high safety of LLM-105. The preparation process is mild in condition, safe, environmentally friendly and easy to amplify, and is expected to be applied to the field of high-energy safe propellant charging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and in particular to a modified 2,6-diamino-3,5-dinitropyrazine-1-oxide-based hybrid energetic material with a high decomposition rate, a preparation method and an application thereof. Background Art

[0002] As a new type of high-energy insensitive explosive, the crystal structure of 2,6-diamino-3,5-dinitropyrazine-1-oxide (LLM-105) is wavy and layered, with a large number of intermolecular π-π conjugation and intramolecular hydrogen bonding. It shows excellent safety against abnormal stimuli such as heat, static electricity, impact, and friction. Its mechanical sensitivity and thermal sensitivity are close to those of "wood explosive" triaminotrinitrobenzene (TATB), while its detonation performance is better than that of TATB (US Patent, UCRL. JC. 142918, 2001; Annual Conference of ICT. Karlsrnhe, Germany, 2002; Journal of Physics: Conference Series 2478(3) 2023; Cryst Growth Des 23(9) 2023 6275-6289.). According to public literature reports, the United States has been exploring the application of LLM-105 in explosives since 2000 (LLNL report UCRL-PRES-145524; LLNL report UCRL-CONF-212824), and the representative application field is the cruise missile W80 model booster (LLNL-TR-667207 CODT-2014-0933; LLNL-TR-668916 CODT-2014-0699; Science & Technology Review, LLNL, October-November 2018). However, there are few reports on the improvement of LLM-105 energy release efficiency in existing literature, and the improvement is limited, which brings certain challenges to the application of LLM-105-based explosives in the field of propellants. Therefore, the development of an LLM-105-based composite energetic material with a greatly improved energy release rate is particularly important in the field of propellants and has application prospects.

[0003] In the prior art, nano LLM-105 was prepared by ultrasound-assisted microfluidic technology. Compared with the raw material, the thermal decomposition temperature of nano LLM-105 was reduced by 2.11~5.69℃; at the same time, a method for preparing cubic short rod-shaped LLM-105 was disclosed, which made the thermal decomposition peak temperature of LLM-105 advance from 350℃ to 343℃. The decomposition rate of LLM-105 can also be regulated by adding a catalyst. The literature reports that adding Al / Ti amorphous alloy powder as a catalyst to LLM-105 reduces its thermal decomposition activation energy by 41.664 kJ / mol; ZIF-90 is also used in this field as a negative combustion rate catalyst to lag the thermal decomposition temperature of LLM-105 by 6.4℃, thereby improving its thermal stability. However, there are few studies on improving the decomposition rate of LLM-105, and the improvement effect is limited. Summary of the invention

[0004] In view of the deficiencies in the above-mentioned background technology, the present invention aims at the difficulty in significantly improving the thermal decomposition rate of LLM-105 in the prior art. The present invention provides a modified 2,6-diamino-3,5-dinitropyrazine-1-oxide-based hybrid energetic material with a high decomposition rate, a preparation method and an application. The present invention generates a high-nitrogen two-dimensional material TAGP by cross-linking glyoxal (or glutaraldehyde) with triaminoguanidine nitrate (TAGN). TAGP is used as a hybrid material to induce LLM-105 to crystallize under its confined constraint, thereby achieving the growth of high-density LLM-105. The thermal decomposition rate of this product can be significantly improved.

[0005] The first object of the present invention is to provide a method for preparing a modified 2,6-diamino-3,5-dinitropyrazine-1-oxide-based hybrid energetic material with a high decomposition rate, comprising the following steps: dissolving triaminoguanidine nitrate in an organic solvent to obtain a triaminoguanidine nitric acid solution; Add LLM-105 to the triaminoguanidine nitric acid solution, mix well, add an aldehyde solvent, react at 140-150°C for 1-2 hours to obtain a reaction solution; An anti-solvent is added to the reaction solution to precipitate a solid product, thereby obtaining a modified 2,6-diamino-3,5-dinitropyrazine-1-oxide-based hybrid energetic material with a high decomposition rate.

[0006] Preferably, the mass fraction of the triaminoguanidine nitrate in LLM-105 is 0.5-5%.

[0007] Preferably, the molar ratio of the triaminoguanidine nitrate to the aldehyde solvent is 1:2-6.

[0008] Preferably, the organic solvent is dimethyl sulfoxide; and the aldehyde solvent is glyoxal or glutaraldehyde.

[0009] Preferably, the triaminoguanidine nitric acid solution is prepared by adding triaminoguanidine nitrate to an organic solvent and stirring at 140-150° C. for 15-30 minutes to completely dissolve the triaminoguanidine nitrate.

[0010] Preferably, the temperature of the reaction solution is set to 25-100° C. when the anti-solvent is added, wherein the anti-solvent is deionized water or ethanol.

[0011] Preferably, the dropwise acceleration rate of the anti-solvent is 0.5 to 10 mL / min.

[0012] Preferably, after the solid product is precipitated, it is filtered and dried to obtain a modified 2,6-diamino-3,5-dinitropyrazine-1-oxide-based hybrid energetic material with a high decomposition rate.

[0013] The second object of the present invention is to provide a modified 2,6-diamino-3,5-dinitropyrazine-1-oxide-based hybrid energetic material with a high decomposition rate.

[0014] The third object of the present invention is to provide a modified 2,6-diamino-3,5-dinitropyrazine-1-oxide-based hybrid energetic material with a high decomposition rate for use in high-energy safety propellant charges.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a modified 2,6-diamino-3,5-dinitropyrazine-1-oxide-based hybrid energetic material with a high decomposition rate, a preparation method and an application thereof. The present invention cross-links TAGN with glyoxal to obtain a two-dimensional high-nitrogen material, and LLM-105 grows under the confinement constraint of this two-dimensional high-nitrogen material to obtain qy-LLM-105. The LLM-105-based composite energetic material provided by the present invention has the characteristics of greatly improved thermal decomposition rate. Compared with the LLM-105 raw material, the decomposition rate is increased by 50%, and the composite energetic material takes into account the high safety of LLM-105. The present invention mainly shortens the reaction process of qy-LLM-105 decomposition under the catalytic action of the two-dimensional material TAGP, thereby increasing the decomposition rate and having a lower activation energy. The preparation process involved in the present invention has mild conditions, is safe and environmentally friendly, and is easy to scale up, and is expected to be applied to the field of high-energy safety propellant charges.

[0016] The invention has a simple process and low raw material cost. On the one hand, the decomposition rate of LLM-105 can be greatly improved, and on the other hand, the density of LLM-105 can be improved. By adjusting the process conditions, products with different reactivity can be obtained. Since TAGP itself contains energy, its decomposition rate can be adjusted under the premise of maintaining the original energy level of LLM-105. The invention provides a new technical approach for adjusting the decomposition rate of energetic materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Scanning electron micrographs of the LLM-105-based hybrid energetic materials with high decomposition rates prepared in Examples 1-6.

[0018] Figure 2 X-ray diffraction patterns of LLM-105-based hybrid energetic materials with high decomposition rates prepared in Examples 1-6.

[0019] Figure 3 DSC analysis chart of LLM-105-based hybrid energetic materials with high decomposition rate prepared in Examples 1-6. DETAILED DESCRIPTION

[0020] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention.

[0021] The present invention aims at the difficulty in significantly improving the thermal decomposition rate of LLM-105 in the prior art. The present invention discloses a LLM-105-based composite energetic material with rapid decomposition characteristics and a preparation method thereof. By introducing an energetic catalyst, the thermal decomposition rate of LLM-105 is significantly improved. The reaction conditions are mild, safe and environmentally friendly, and easy to scale up. At the same time, the composite material takes into account the high safety of LLM-105 and has good application prospects in the field of high-energy safety propellant charges.

[0022] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a modified 2,6-diamino-3,5-dinitropyrazine-1-oxide-based hybrid energetic material (LLM-105-based hybrid energetic material) with a high decomposition rate, comprising the following steps: dissolving triaminoguanidine nitrate in an organic solvent to obtain a triaminoguanidine nitric acid solution; Add LLM-105 to the triaminoguanidine nitric acid solution, mix well, add an aldehyde solvent, react at 140-150°C for 1-2 hours to obtain a reaction solution; An anti-solvent is added to the reaction solution to precipitate a solid product, thereby obtaining a modified 2,6-diamino-3,5-dinitropyrazine-1-oxide-based hybrid energetic material with a high decomposition rate.

[0023] The present invention first obtains an energetic high-nitrogen two-dimensional material (TAGP) formed by cross-linking triaminoguanidine nitrate (TAGN) and an aldehyde solvent, and then uses TAGP as a template material to induce LLM-105 crystallization, and obtains an LLM-105 / TAGP composite energetic material through separation, washing, and drying. The LLM-105-based composite energetic material provided by the present invention has the characteristic of greatly improving the thermal decomposition rate. Compared with the LLM-105 raw material, the decomposition rate is increased by 50%. At the same time, the composite energetic material takes into account the high safety of LLM-105. The preparation process involved in the present invention has mild conditions, is safe and environmentally friendly, and is easy to scale up, and is expected to be applied to the field of high-energy safety propellant charges.

[0024] Wherein, the mass fraction of triaminoguanidine nitrate in LLM-105 is 0.5-5%.

[0025] The molar ratio of the triaminoguanidine nitrate to the aldehyde solvent is 1:2-6.

[0026] The organic solvent is dimethyl sulfoxide; the aldehyde solvent is glyoxal or glutaraldehyde.

[0027] The triaminoguanidine nitric acid solution is prepared by adding triaminoguanidine nitrate into an organic solvent, stirring at 140-150° C. for 15-30 minutes to completely dissolve the solvent.

[0028] When adding the anti-solvent, the temperature of the reaction solution is set to 25-100° C., wherein the anti-solvent is deionized water or ethanol.

[0029] The dropwise acceleration rate of the antisolvent is 0.5-10 mL / min.

[0030] After the solid product is precipitated, it is filtered and dried to obtain a modified 2,6-diamino-3,5-dinitropyrazine-1-oxide-based hybrid energetic material with a high decomposition rate.

[0031] In one embodiment, a method for preparing a LLM-105-based hybrid energetic material with a high decomposition rate is characterized by the following steps: Step 1: Add TAGN to dimethyl sulfoxide (DMSO) solution and stir at 140-150°C for 20 minutes to completely dissolve it; Step 2: Add LLM-105 to the solution prepared in step 1 and continue stirring for 30 minutes to allow it to completely dissolve; Step 3: Add glyoxal or glutaraldehyde to the solution prepared in step 2, and react at 140-150° C. for 1 hour; Step 4: adding an anti-solvent dropwise to the solution prepared in step 3 to precipitate a solid product; Step 5: Filter and dry the solid product obtained in step 4 to obtain the LLM-105-based composite energetic material (qy-LLM-105).

[0032] The mass fraction of TAGN in step 2 is 0.5% to 5%. The molar ratio of glyoxal (or glutaraldehyde) to TAGN in step 3 is 1:1 to 6:1. When the anti-solvent is added dropwise in step 4, the solution is kept warm at 25°C to 100°C. The anti-solvent added dropwise in step 4 is one of deionized water, methanol, and ethanol. The dropwise acceleration rate of the anti-solvent in step 4 is 0.5 mL / min to 10 mL / min.

[0033] The second aspect of the present invention provides a modified 2,6-diamino-3,5-dinitropyrazine-1-oxide-based hybrid energetic material with a high decomposition rate.

[0034] The third aspect of the present invention provides a modified 2,6-diamino-3,5-dinitropyrazine-1-oxide-based hybrid energetic material with a high decomposition rate for use in high-energy safety propellant charges.

[0035] It should be noted that the experimental methods used in the present invention are all conventional methods unless otherwise specified; the reagents and materials used are all commercially available unless otherwise specified.

[0036] Example 1 A method for preparing a LLM-105-based hybrid energetic material with a high decomposition rate comprises the following process steps: Dissolution of TAGN: Weigh 0.08 g TAGN and add it to 30 mL DMSO. Heat the mixture to 140°C in an oil bath and stir for 20 min until TAGN is completely dissolved.

[0037] Dissolution of LLM-105: Weigh 2.925 g of LLM-105 (the mass fraction of TAGN is 2.5%) and add it to the dissolved TAGN solution. Stir continuously for 30 min to completely dissolve it to obtain a TAGN / LLM-105 solution. Generation of high-nitrogen two-dimensional materials: 0.10 mL of glyoxal (the molar ratio of glyoxal to TAGN is 4:1) was added to the dissolved TAGN / LLM-105 solution and stirred at 140 °C for 1 h to react and generate high-nitrogen two-dimensional materials.

[0038] Crystallization of qy-LLM-105: The solution was kept at 100°C, and deionized water at 90°C was added at a rate of 6 mL / min through a peristaltic pump to precipitate a solid product.

[0039] Collection of the product: The product was washed with deionized water, filtered and vacuum freeze-dried to obtain qy-LLM-105 in yellow powder form.

[0040] The qy-LLM-105 prepared in Example 1 was subjected to scanning electron microscopy analysis. Figure 1 As shown, its crystal morphology is overlapping prisms.

[0041] The qy-LLM-105 prepared in Example 1 was subjected to XRD analysis. Figure 2 As shown, compared with the original LLM-105, the diffraction peak intensity of Example 1 at 11.2° and 33.9° is significantly reduced, and the diffraction peak intensity at 22.4° is significantly enhanced.

[0042] The qy-LLM-105 prepared in Example 1 was subjected to vacuum density analysis (gas replacement method), and the density test result was 1.9282 g / cm 3 .

[0043] The qy-LLM-105 prepared in Example 1 was subjected to DSC analysis. The results are as follows: Figure 3 shown.

[0044] The activation energy of qy-LLM-105 prepared in Example 1 was calculated, and the results are shown in Table 1. Its activation energy is lower than that of the original LLM-105, indicating that the reaction rate is faster.

[0045] Example 2 A method for preparing a LLM-105-based hybrid energetic material with a high decomposition rate comprises the following process steps: Dissolution of TAGN: Weigh 0.02 g TAGN and add it to 30 mL DMSO. Heat the mixture to 140°C in an oil bath and stir for 20 min until TAGN is completely dissolved.

[0046] Dissolution of LLM-105: Weigh 2.985 g of LLM-105 (the mass fraction of TAGN is 0.5%) and add it to the dissolved TAGN solution. Stir continuously for 30 min to completely dissolve it to obtain a TAGN / LLM-105 solution. Generation of high-nitrogen two-dimensional materials: 0.007 mL of glyoxal (the molar ratio of glyoxal to TAGN is 1:1) was added to the dissolved TAGN / LLM-105 solution and stirred at 140 °C for 1 h to react and generate high-nitrogen two-dimensional materials.

[0047] Crystallization of qy-LLM-105: The solution was kept at 100°C, and deionized water at 90°C was added at a rate of 6 mL / min through a peristaltic pump to precipitate a solid product.

[0048] Product collection: The product was washed with deionized water, filtered and vacuum freeze-dried to obtain bright yellow powder qy-LLM-105.

[0049] The qy-LLM-105 prepared in Example 2 was subjected to scanning electron microscopy analysis. Figure 1 As shown, its crystal morphology is overlapping prisms.

[0050] The qy-LLM-105 prepared in Example 2 was subjected to XRD analysis. Figure 2 As shown, compared with the original LLM-105, the diffraction peak intensity of Example 2 at 11.2° and 33.9° is significantly reduced, and the diffraction peak intensity at 22.4° is significantly enhanced.

[0051] The qy-LLM-105 prepared in Example 2 was subjected to vacuum density analysis (gas replacement method), and the density test result was 1.9176 g / cm 3 , the density improvement effect is not significant enough.

[0052] The qy-LLM-105 prepared in Example 2 was subjected to DSC analysis. The results are as follows Figure 3 shown.

[0053] The activation energy of qy-LLM-105 prepared in Example 2 was calculated, and the results are shown in Table 1. Its activation energy is lower than that of the original LLM-105, indicating that the reaction rate is faster.

[0054] Example 3 A method for preparing a LLM-105-based hybrid energetic material with a high decomposition rate comprises the following process steps: Dissolution of TAGN: Weigh 0.15 g TAGN and add it to 30 mL DMSO. Heat the mixture to 140°C in an oil bath and stir for 20 min until TAGN is completely dissolved.

[0055] Dissolution of LLM-105: Weigh 2.85 g of LLM-105 (the mass fraction of TAGN is 5%) and add it to the dissolved TAGN solution. Stir continuously for 30 min to completely dissolve it to obtain a TAGN / LLM-105 solution. Generation of high-nitrogen two-dimensional materials: 0.31 mL of glyoxal (the molar ratio of glyoxal to TAGN is 6:1) was added to the dissolved TAGN / LLM-105 solution and stirred at 140 °C for 1 h to react and generate high-nitrogen two-dimensional materials.

[0056] Crystallization of qy-LLM-105: The solution was kept at 100°C, and deionized water at 90°C was added at a rate of 6 mL / min through a peristaltic pump to precipitate a solid product.

[0057] Product collection: The product was washed with deionized water, filtered and vacuum freeze-dried to obtain bright yellow powder qy-LLM-105.

[0058] The qy-LLM-105 prepared in Example 3 was subjected to scanning electron microscopy analysis. Figure 1 As shown, its crystal structure is prismatic and the agglomeration phenomenon is obvious.

[0059] The qy-LLM-105 prepared in Example 3 was subjected to XRD analysis. Figure 2 As shown, compared with the original LLM-105, the diffraction peak intensity of Example 3 at 11.2° and 33.9° is significantly reduced, and the diffraction peak intensity at 22.4° is significantly enhanced.

[0060] The qy-LLM-105 prepared in Example 3 was subjected to vacuum density analysis (gas replacement method), and the density test result was 1.9577 g / cm 3 , which is slightly lower than that of Example 5.

[0061] The qy-LLM-105 prepared in Example 3 was subjected to DSC analysis. The results are as follows Figure 3 shown.

[0062] The activation energy of qy-LLM-105 prepared in Example 3 was calculated, and the results are shown in Table 1. Its activation energy is greatly reduced compared with the original LLM-105, indicating that the reaction rate is faster.

[0063] The elemental analysis of Example 3 is shown in Table 2.

[0064] The combustion heat test of Example 3 showed a result of 9.61 kJ / g, and its formation enthalpy was calculated to be -10.31 kJ / mol.

[0065] Example 4 A method for preparing a LLM-105-based hybrid energetic material with a high decomposition rate comprises the following process steps: Dissolution of TAGN: Weigh 0.15 g TAGN and add it to 30 mL DMSO. Heat the mixture to 150°C in an oil bath and stir for 20 min until TAGN is completely dissolved.

[0066] Dissolution of LLM-105: Weigh 2.85 g of LLM-105 (the mass fraction of TAGN is 5%) and add it to the dissolved TAGN solution. Stir continuously for 30 min to completely dissolve it to obtain a TAGN / LLM-105 solution. Generation of high-nitrogen two-dimensional materials: 0.21 mL of glyoxal (the molar ratio of glyoxal to TAGN is 4:1) was added to the dissolved TAGN / LLM-105 solution and stirred at 150 °C for 1 h to react and generate high-nitrogen two-dimensional materials.

[0067] Crystallization of qy-LLM-105: The solution was kept at 100°C, and deionized water at 90°C was added at a rate of 6 mL / min through a peristaltic pump to precipitate a solid product.

[0068] Product collection: The product was washed with deionized water, filtered and vacuum freeze-dried to obtain brown-yellow powder qy-LLM-105.

[0069] The qy-LLM-105 prepared in Example 4 was subjected to scanning electron microscopy analysis. Figure 1 As shown, its crystal structure is prismatic and has agglomeration phenomenon.

[0070] The qy-LLM-105 prepared in Example 4 was subjected to XRD analysis. Figure 2 As shown, compared with the original LLM-105, the diffraction peak intensity of Example 4 at 11.2° and 33.9° is significantly reduced, and the diffraction peak intensity at 22.4° is significantly enhanced.

[0071] The qy-LLM-105 prepared in Example 4 was subjected to vacuum density analysis (gas replacement method), and the density test result was 1.9465 g / cm 3 .

[0072] The qy-LLM-105 prepared in Example 4 was subjected to DSC analysis. The results are as follows Figure 3 shown.

[0073] The activation energy of qy-LLM-105 prepared in Example 4 was calculated, and the results are shown in Table 1. Its activation energy is greatly reduced compared with the original LLM-105, indicating that the reaction rate is faster.

[0074] Example 5 A method for preparing a LLM-105-based hybrid energetic material with a high decomposition rate comprises the following process steps: Dissolution of TAGN: Weigh 0.15 g TAGN and add it to 30 mL DMSO. Heat the mixture to 140°C in an oil bath and stir for 20 min until TAGN is completely dissolved.

[0075] Dissolution of LLM-105: Weigh 2.85 g of LLM-105 (the mass fraction of TAGN is 5%) and add it to the dissolved TAGN solution. Stir continuously for 30 min to completely dissolve it to obtain a TAGN / LLM-105 solution. Generation of high-nitrogen two-dimensional materials: 0.18 mL of glutaraldehyde (the molar ratio of glutaraldehyde to TAGN is 2:1) was added to the dissolved TAGN / LLM-105 solution and stirred at 140°C for 1 h to react and generate high-nitrogen two-dimensional materials.

[0076] Crystallization of qy-LLM-105: The solution was kept at 100°C, and deionized water at 25°C was added at a rate of 6 mL / min through a peristaltic pump to precipitate a solid product.

[0077] Product collection: The product was washed with deionized water, filtered and vacuum freeze-dried to obtain bright yellow powder qy-LLM-105.

[0078] The qy-LLM-105 prepared in Example 5 was subjected to scanning electron microscopy analysis. Figure 1 As shown, its crystal structure is prismatic and has agglomeration phenomenon.

[0079] The qy-LLM-105 prepared in Example 5 was subjected to XRD analysis. Figure 2 As shown, compared with the original LLM-105, the diffraction peak intensity of Example 5 at 11.2° and 33.9° is significantly reduced, and the diffraction peak intensity at 22.4° is significantly enhanced.

[0080] The qy-LLM-105 prepared in Example 5 was subjected to vacuum density analysis (gas replacement method), and its density test result was 1.9385 g / cm 3 , which is lower than that of Example 9, indicating that the effect of TAGN-glutaraldehyde crosslinking agent on improving the density of LLM-105 is not as good as that of TAGN-glyoxal crosslinking agent.

[0081] The qy-LLM-105 prepared in Example 5 was subjected to DSC analysis. The results are as follows Figure 3 shown.

[0082] The activation energy of qy-LLM-105 prepared in Example 5 was calculated, and the results are shown in Table 1. Its activation energy is greatly reduced compared with the original LLM-105, indicating that the reaction rate is faster.

[0083] Example 6 A method for preparing a LLM-105-based hybrid energetic material with a high decomposition rate comprises the following process steps: Dissolution of TAGN: Weigh 0.15 g TAGN and add it to 30 mL DMSO. Heat the mixture to 140°C in an oil bath and stir for 20 min until TAGN is completely dissolved.

[0084] Dissolution of LLM-105: Weigh 2.85 g of LLM-105 (the mass fraction of TAGN is 5%) and add it to the dissolved TAGN solution. Stir continuously for 30 min to completely dissolve it to obtain a TAGN / LLM-105 solution. Generation of high-nitrogen two-dimensional materials: 0.10 mL of glyoxal (the molar ratio of glyoxal to TAGN is 2:1) was added to the dissolved TAGN / LLM-105 solution and stirred at 140 °C for 1 h to react and generate high-nitrogen two-dimensional materials.

[0085] Crystallization of qy-LLM-105: The solution was kept at 100°C, and ethanol at 25°C was added at a rate of 6 mL / min through a peristaltic pump to precipitate a solid product.

[0086] Product collection: The product was washed with deionized water, filtered and vacuum freeze-dried to obtain bright yellow powder qy-LLM-105.

[0087] The qy-LLM-105 prepared in Example 6 was subjected to scanning electron microscopy analysis. Figure 1 As shown, its crystal structure is a prism with a relatively large aspect ratio, and ethanol has a better dispersion effect on the crystals.

[0088] The qy-LLM-105 prepared in Example 6 was subjected to XRD analysis. Figure 2 As shown, compared with the original LLM-105, the diffraction peak intensity of Example 6 at 11.2° and 33.9° is significantly reduced, and the diffraction peak intensity at 22.4° is significantly enhanced.

[0089] The qy-LLM-105 prepared in Example 6 was subjected to vacuum density analysis (gas replacement method), and its density test result was 1.9755 g / cm 3 , which is improved compared with Example 9, indicating that using ethanol as anti-solvent can better improve the density.

[0090] The qy-LLM-105 prepared in Example 6 was subjected to DSC analysis. The results are as follows: Figure 3 shown.

[0091] The activation energy of qy-LLM-105 prepared in Example 6 was calculated, and the results are shown in Table 1. Its activation energy is greatly reduced compared with the original LLM-105, indicating that the reaction rate is faster.

[0092] Table 1 shows the activation energy calculation results of the LLM-105-based hybrid energetic materials with high decomposition rates prepared in Examples 1-6.

[0093]

[0094] Table 2 shows the elemental analysis results of the LLM-105-based hybrid energetic material with high decomposition rate prepared in Example 3.

[0095]

[0096] The present invention describes preferred embodiments and their effects. However, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0097] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a modified 2,6-diamino-3,5-dinitropyrazine-1-oxide-based hybrid energetic material with a high decomposition rate, characterized in that: The following steps are involved: dissolving triaminoguanidine nitrate in an organic solvent to obtain a triaminoguanidine nitric acid solution; Add LLM-105 to the triaminoguanidine nitric acid solution, mix well, add an aldehyde solvent, react at 140-150°C for 1-2 hours to obtain a reaction solution; An anti-solvent is added to the reaction solution to precipitate a solid product, thereby obtaining a modified 2,6-diamino-3,5-dinitropyrazine-1-oxide-based hybrid energetic material with a high decomposition rate.

2. The method for preparing the modified 2,6-diamino-3,5-dinitropyrazine-1-oxide-based hybrid energetic material with a high decomposition rate according to claim 1, characterized in that: The mass fraction of the triaminoguanidine nitrate in LLM-105 is 0.5-5%.

3. The method for preparing the modified 2,6-diamino-3,5-dinitropyrazine-1-oxide-based hybrid energetic material with high decomposition rate according to claim 1, characterized in that: The molar ratio of the triaminoguanidine nitrate to the aldehyde solvent is 1:2-6.

4. The method for preparing the modified 2,6-diamino-3,5-dinitropyrazine-1-oxide-based hybrid energetic material with high decomposition rate according to claim 1, characterized in that: The organic solvent is dimethyl sulfoxide; the aldehyde solvent is glyoxal or glutaraldehyde.

5. The method for preparing the modified 2,6-diamino-3,5-dinitropyrazine-1-oxide-based hybrid energetic material with high decomposition rate according to claim 1, characterized in that: The triaminoguanidine nitric acid solution is prepared by adding triaminoguanidine nitrate into an organic solvent, stirring at 140-150° C. for 15-30 minutes to completely dissolve the solvent.

6. The method for preparing the modified 2,6-diamino-3,5-dinitropyrazine-1-oxide-based hybrid energetic material with high decomposition rate according to claim 1, characterized in that: When adding the anti-solvent, the temperature of the reaction solution is set to 25-100° C., wherein the anti-solvent is deionized water or ethanol.

7. The method for preparing the modified 2,6-diamino-3,5-dinitropyrazine-1-oxide-based hybrid energetic material with high decomposition rate according to claim 1, characterized in that: The dropwise acceleration rate of the antisolvent is 0.5-10 mL / min.

8. The method for preparing the modified 2,6-diamino-3,5-dinitropyrazine-1-oxide-based hybrid energetic material with high decomposition rate according to claim 1, characterized in that: After the solid product is precipitated, it is filtered and dried to obtain a modified 2,6-diamino-3,5-dinitropyrazine-1-oxide-based hybrid energetic material with a high decomposition rate.

9. A modified 2,6-diamino-3,5-dinitropyrazine-1-oxide-based hybrid energetic material with a high decomposition rate obtained by the method according to any one of claims 1 to 8.

10. Use of the modified 2,6-diamino-3,5-dinitropyrazine-1-oxide-based hybrid energetic material with a high decomposition rate as claimed in claim 9 in high-energy safety propellant charges.

Citation Information

Patent Citations

  • Preparation method of high-nitrogen modified ammonium nitrate explosive crystal doped with 2D conjugated structure

    CN108424339A

  • Preparation method of HMX / ANPyO eutectic crystal under two-dimensional material confinement doping condition

    CN112266311A

  • Energy-containing burning rate inhibitor for solid propellant and preparation method of energy-containing burning rate inhibitor

    CN115160091A

  • Method for preparing HMX two-dimensional crystal through high-nitrogen skeleton induction

    CN115785012A